Emoticons as a medium for channeling politeness within American and Japanese online blogging communities. (May 2016) - Kavanagh, Barry
Abstract: This paper aims to examine how Brown and Levinson's (1987) politeness strategies are channeled through the medium of emoticons in American and Japanese online personal weblog comments. Results showed that although American and Japanese blog comment writers both utilized emoticons that helped to convey positive politeness strategies Japanese used them significantly more than Americans. It is argued that this challenges the notion of Japanese as being a negative orientated culture within this online blog community. Highlights: Outline of how emoticons work in American and Japanese blogging communities. Show how emoticons channel politeness for relational online communication. Emoticon usage challenges the notion that Japanese is a negative politeness culture.